2006
DOI: 10.1080/13607860500409385
|View full text |Cite
|
Sign up to set email alerts
|

Falklands War veterans’ perceptions of social support and the reconciliation of traumatic memories

Abstract: The current paper focused on the role social support plays in the reconciliation of traumatic memories. Four currently serving, male Royal Marines ranging from 40-42 years participated in semi-structured one-to-one interviews that explored perceptions of social support. Using thematic analysis, comradeship was found to be important in terms of maintaining support networks. However, this resource was used to avoid the reconciliation of traumatic memories. Social support from family members was sought when veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…Recent research has demonstrated that the receipt of gratitude can mitigate negative consequences and posttraumatic stress responses after war (Burnell, Coleman & Hunt, 2006;Hautamäki & Coleman, 2001). In addition, gratitude may promote motivation, daily selfregard and the pursuit of constructive, satisfying, and rewarding social activities, leading to personal growth (Kashdan, Uswatte & Julian, 2006;Wood, Joseph & Maltby, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that the receipt of gratitude can mitigate negative consequences and posttraumatic stress responses after war (Burnell, Coleman & Hunt, 2006;Hautamäki & Coleman, 2001). In addition, gratitude may promote motivation, daily selfregard and the pursuit of constructive, satisfying, and rewarding social activities, leading to personal growth (Kashdan, Uswatte & Julian, 2006;Wood, Joseph & Maltby, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Schok and colleagues (2010) describe a comradeship that was developed between soldiers on a mission in Cambodia where one soldier reports: "yes we went through fire for each other" (Schok, 2010, p.289). In the Burnell et al 2006 study, the comradeship during the Falklands War conflict was very important for soldiers and the bond that was created through shared experiences were expressed as follows: "There is a bond you form with these people... because you've been through the same experience that never goes away" (Burnell et al, 2006, p. 285). Kilshaw (2004) also explores the comradeship of the Gulf War veterans in the United Kingdom who defined themselves as a group sharing a physical illness, further categorizing their experiences within the framework of an illness narrative: "Everyone WAR EXPERIENCES, SHARED NARRATIVES, SHIFTING IDENTITIES 21 can associated with each other with each other's symptoms..…”
Section: Forming Bonds Through Collective Narrative and Experiencesmentioning
confidence: 99%
“…What other military personnel have experienced in wartime adds to the narrative of war zone stories that are not shared in quantitative studies, but can still provide insight into the problems faced by personnel and the collateral impact of war experience (such as working in WAR EXPERIENCES, SHARED NARRATIVES, SHIFTING IDENTITIES 20 dangerous environments) which can remain unknown or undiscovered for various reasons related to diagnosis, delayed onset of symptoms or other stressors encountered at home (Burnell, et al, 2006;Kilshaw, 2004). Vogt and colleagues studied Vietnam War veterans to compare the levels of satisfaction and attainment between personnel who served in military campaigns in Vietnam, and those who had never served at all (Vogt, King, King, Savarese & Suvak, 2004).…”
Section: Military Experience Described As Work or A Jobmentioning
confidence: 99%
See 2 more Smart Citations